Menyelisik Dinamika Implementasi Padi Organik Di Kabupaten Tasikmalaya Dari Tahun 2017-2023 - Indriana, Hana; Rizki Aditya Putra (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The growing public interest in organic food has sparked a movement towards organic agriculture since the early 2000s, driven by various non-governmental organizations (NGOs). This surge in interest prompted policymakers to develop guidelines and regulations to support organic farming. Tasikmalaya Regency is one of the pioneers in the implementation of organic agriculture that has been able to produce and cultivate organic rice since 2006. This study aims to investigate the factors that affect the implementation of organic rice farming in Tasikmalaya during 2017-2023 and formulate policies that can be proposed to improve the implementation. The results of the study show that socio-economic, technical, production quality, and adaptation to external changes such as the COVID-19 pandemic, affect the dynamics of organic rice farming in Tasikmalaya. Recommended policies include institutional strengthening, capacity building and farmer education, infrastructure development and market access, and providing economic and financial incentives.